Raden Mattaher sebagai Tonggak Sejarah Perjuangan Kemerdekaan Indonesia di Jambi - Nirwan II Yasin; Miftahul Jannah (LP4MK STKIP PGRI Lubuklinggau, 2021)
The purpose of writing this article is to be able to find out the struggle of the Jambi hero during Indonesian independence, Raden Mataher. Raden Mattaher was a Jambi warlord who was very famous and feared by the Dutch. After the death of Sultan Thaha Saifuddin in 1904, the command of the resistance against the Dutch in Jambi was continued by Raden Mattaher. He has shown to be a knight, brave, smart, and clever at strategizing. The writing method used is to take historical writing steps. First, heuristics (data collection), namely by using the literature study method and the internet. Second, third verification, interpretation (analyzing data that has been verified). Fourth, historiography (writing data that has been analyzed). Interview method by obtaining information by asking history teachers. Raden Mattaher is one of the mighty heroes of Jambi. In expelling the Dutch he never wanted to give up. Good war tactics. He is also one of the warlords who are feared by the Dutch. Not only a warrior, he is also a diligent worshiper with a strong faith. As Indonesians, we should be proud of having a hero who is willing to sacrifice body and soul. We as young generations should have a high enthusiasm for learning to gain knowledge so that we can continue the struggle that was carried out by Raden Mattaher.